2012
DOI: 10.7243/2050-0866-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Glycemia Targeted Specialized Nutrition (GTSN) improves postprandial glycemia and GLP-1 with similar appetitive responses compared to a healthful whole food breakfast in persons with type 2 diabetes: a randomized, controlled trial

Abstract: Background: For people with type 2 diabetes mellitus (T2DM), the frequency and/or composition of the morning meal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
4
9
0
Order By: Relevance
“…This study shows that postprandial plasma glucose is significantly lower after either of the two DSNFs in comparison to OM. This observation is in line with previous studies which used similar formulas [ 13 , 14 , 19 ]. The low glycemic index of most DSNFs partially contributes to this effect [ 14 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study shows that postprandial plasma glucose is significantly lower after either of the two DSNFs in comparison to OM. This observation is in line with previous studies which used similar formulas [ 13 , 14 , 19 ]. The low glycemic index of most DSNFs partially contributes to this effect [ 14 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…This difference might explain the difference in GLP-1 response. It also confirms previous observations that the amount and the type of fat and carbohydrates play important role in promoting GLP-1 secretion [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specialized diabetes-specific formulas (DSF) are designed using low glycemic index and slowly digested carbohydrates and monosaturated fatty acids to support glycemic control [81][82][83]. Systematic reviews and meta-analyses have shown that DSF as part of lifestyle interventions effectively improves glycemic control and reduces cardiometabolic risks [84,85].…”
Section: Evidence For the Use Of Complete And Balanced Nutritional Sumentioning
confidence: 99%
“…Research design and methods Adults (n=81) with T2D managed by oral medications were studied in a randomized, open-label, three-group parallel study design. The study was conducted in two phases over 14 days: Baseline (days 1-6), during which study participants consumed their habitual self-selected diets (SSD), followed by the Intervention (days [7][8][9][10][11][12][13][14], during which participants were randomized as follows: (1) SSD group received no study product (n=32); (2) DSNS breakfast/afternoon snack (Bkfst/AS) group consumed one DSNS as a breakfast meal replacement and a second to replace their mid-afternoon snack (n=24); (3) DSNS breakfast/prebed snack (Bkfst/ PBS) group consumed one DSNS as a breakfast meal replacement and added a second as a prebed snack (n=25). Glucose was assessed by CGM throughout the study.…”
mentioning
confidence: 99%